Pattern of Prophylactic Antibiotic Prescribing in Surgical Patients at the University of Indonesia Hospital - Tita Kusuma Wardani; Retnosari Andrajati; M. Arza Putra; Anggara Gilang Dwiputra (Eduvest - Journal of Universal Studies, 2025)
Surgical procedures involve interventions that may compromise tissue integrity, necessitating prophylactic antibiotics to prevent surgical site infections (SSIs). Proper timing, selection, and administration of antibiotics are crucial to achieving optimal therapeutic outcomes. This study aimed to evaluate the prescribing patterns of prophylactic antibiotics in patients undergoing surgical procedures at the University of Indonesia Hospital and assess adherence to established guidelines. A retrospective observational study analyzed medical records of patients who underwent surgery. Data collected included the type of antibiotics prescribed, timing of administration, dosage, duration, and adherence to national and international guidelines. Descriptive statistics were used to summarize the findings. The study analyzed 213 surgical patients at the University of Indonesia Hospital in September 2024. Prophylactic antibiotics were prescribed in 90.61% of cases, predominantly Cefazolin (86.48%), with doses of 2 g (76.12%) and 1 g (10.36%). Most patients (97.93%) received antibiotics 30–60 minutes pre-incision. All antibiotics were administered intravenously with research results, 4.29% were affected by IDO. These findings highlight overall adherence to prophylactic antibiotic guidelines, with minor deviations in timing and dosage observed in a few cases. Optimal prescribing practices were achieved in most surgical patients to reduce the risk of SSI.